Prevalencia de anemia ferropénica y su relación con el estado nutricional en niños y niñas pre-escolares del Centro de Salud “22 de noviembre” del Cantón Milagro, Provincia del Guayas del periodo mayo a septiembre del 2019. - Freire Junco, Estefany Gisell (2019)
As a place of study, the 22 de November Health Center, located in the Milagro canton in the province of Guayas, has been selected. Our research work the general objective is to determine the prevalence of iron deficiency anemia and its relationship with nutritional status in preschool children. The methods used were: inductive and analysis. Inductive method, since we rely on observation in order to reach a conclusion and analysis because we study each of its elements intensively. The prevalence of iron deficiency anemia is 85% taking into account that the population of our study is 117 infants and its sample is 100 children who are in the preschool stage, therefore, the specific hypothesis is met if it is met. To determine the nutritional status we use the anthropometric indicators T / E and P / T, according to our results they determined that 80% of boys and girls from 3 to 5 years of age had normal weight and the indicator age size will be that 71% boys and girls from 3 to 5 years old, normal size. The results indicate that the highest percentage of our population has a normal nutritional status, therefore our general hypothesis is not fulfilled since there is no relationship between iron deficiency anemia and the nutritional status of preschool children.